ATMOSPHERIC AIR AND PUBLIC HEALTH IN MODERN CONDITIONS - Akhmadalieva Nigora; Sherkuziyeva Guzal; Safarov Mirzoxid (The Conference Hub, 2025)
The quality of atmospheric air has a significant impact on public health. In the context of rapid urbanization, industrial growth, and increasing emissions of harmful substances, the issue of air pollution has become particularly relevant. The main sources of pollution include industrial enterprises, transportation, agricultural activities, and household fuel combustion. Harmful substances such as sulfur dioxide, nitrogen oxides, fine particulate matter (PM10, PM2.5), ozone, carbon monoxide, and heavy metals negatively affect the respiratory and cardiovascular systems, increasing the risk of chronic diseases. The most vulnerable population groups include children, the elderly, and individuals with chronic illnesses. To mitigate the negative impact of polluted air, comprehensive measures are needed, including government regulations, the development of environmentally friendly technologies, the expansion of green spaces, the use of air purification systems, and raising public awareness. Improving air quality is directly linked to the preservation of health and the enhancement of the population’s quality of life.Main Sources of Atmospheric Air Pollution